Structural changes in supercooled Al2O3-Y2O3 liquids. - Wilding, M; Wilson, M; Benmore, C; Weber, J; McMillan, P (2013)
Structural changes in liquids between Al2O3 and Y2O3 are investigated as a function of the composition and during supercooling using high energy X-ray diffraction (HEXRD) techniques combined with containerless aerodynamic levitation. Many-body molecular dynamics simulation techniques utilizing potential models that incorporate anion polarization effects are applied to study the same liquid systems. The X-ray scattering experiments indicate a change in liquid structure during supercooling around a composition 20% Y2O3 (AlY20) that occurs over a narrow temperature interval. We have associated this change in structure with the onset of a liquid-liquid phase transformation. Analysis of the MD simulated structures has allowed the structure changes to be interpreted in terms of Al(3+) and Y(3+) coordination environments and particularly the Y(3+)-Y(3+) structural correlations. We show that the incipient liquid-liquid phase transition behaviour is correlated with local density fluctuations that represent different coordination polyhedra surrounding oxygen ions. The difference in energy and volume associated with this sampling of high and low density basins in the underlying energy landscape is consistent with independent verifications of the volume and enthalpy differences between different amorphous forms. The differences in the high- and low-density configurations match the difference in diffraction patterns observed experimentally.